Legal Efforts to Enhance the Effectiveness of Legal Protection for Victims of Human Trafficking Crimes - Pambudi Pambudi; Ahmad Redi (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effectiveness of legal protection for victims of human trafficking in Indonesia, based on Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. Legal protection for victims encompasses preventive measures, case handling, and the restoration of victims’ rights through available legal mechanisms. The focus of this research is to evaluate how far the existing regulations can provide comprehensive protection for victims—beginning from the victim identification process, through judicial proceedings, and continuing to social rehabilitation and reintegration into society. This study applies a normative juridical method that emphasizes legal norms and regulations in force. It also highlights the importance of synergy among law enforcement agencies, the government, and non-governmental organizations to ensure optimal protection for trafficking victims. The research identifies several challenges in the implementation of legal protection, such as limited human resources and inadequate facilities, lack of public legal awareness, and judicial processes that are often slow and unresponsive to victims’ needs. Another major obstacle is the lack of access to legal aid and recovery services, which are crucial for supporting victims’ reintegration and fulfillment of their human rights. This paper seeks to provide a clearer understanding of the current conditions regarding legal protection for human trafficking victims in Indonesia and to formulate recommendations for more effective and integrated policy improvements. Enhancing legal frameworks and improving inter-agency coordination are essential steps toward ensuring victims receive justice and the protection they are entitled to under human rights principles.